Morphological imaging and T2 and T2* mapping of hip cartilage at 7 Tesla MRI under the influence of intravenous gadolinium. - Lazik-Palm, Andrea; Kraff, Oliver; Geis, Christina; Johst, Sören; Goebel, Juliane; Ladd, Mark; Quick, Harald; Theysohn, Jens; Ladd, Mark E; Quick, Harald H; Theysohn, Jens M (European Radiology, 2016)
Objectives: To investigate the influence of intravenous gadolinium on cartilage T2 and T2* relaxation times and on morphological image quality at 7-T hip MRI.Methods: Hips of 11 healthy volunteers were examined at 7 T. Multi-echo sequences for T2 and T2* mapping, 3D T1 volumetric interpolated breath-hold examination (VIBE) and double-echo steady-state (DESS) sequences were acquired before and after intravenous application of gadolinium according to a delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) protocol. Cartilage relaxation times were measured in both scans. Morphological sequences were assessed quantitatively using contrast ratios and qualitatively using a 4-point Likert scale. Student's t-test, Pearson's correlation (ρ) and Wilcoxon sign-rank test were used for statistical comparisons.Results: Pre- and post-contrast T2 and T2* values were highly correlated (T2: acetabular: ρ = 0.76, femoral: ρ = 0.77; T2*: acetabular: ρ = 0.80, femoral: ρ = 0.72). Gadolinium enhanced contrasts between cartilage and joint fluid in DESS and T1 VIBE according to the qualitative (p = 0.01) and quantitative (p < 0.001) analysis. The delineation of acetabular and femoral cartilage and the labrum predominantly improved with gadolinium.Conclusions: Gadolinium showed no relevant influence on T2 or T2* relaxation times and improved morphological image quality at 7 T. Therefore, morphological and quantitative sequences including dGEMRIC can be conducted in a one-stop-shop examination.Key Points: • Hip cartilage T2 values correlate highly before and after gadolinium at 7 T • Hip cartilage T2* values correlate highly before and after enhancement at 7 T • Morphological hip cartilage imaging benefits from intravenous gadolinium at 7 T • The delineation of acetabular and femoral cartilage can be improved by gadolinium • Morphological and quantitative sequences including dGEMRIC can be combined as a one-stop-shop examination.